Study on the thermal protection performance of superalloy honeycomb panels in high-speed thermal shock environments - Dafang Wu; Anfeng Zhou; Liming Zheng; Bing Pan; Yuewu Wang (Theoretical and Applied Mechanics Letters, 2014)
The thermal protection performance of superalloy honeycomb structure in high-temperature environments are important for thermal protection design of high-speed aircrafts. By using a self-developed transient aerodynamic thermal simulation system, the thermal protection performance of superalloy honeycomb panel was tested in this paper at different transient heating rates ranging from 5°C/s to 30°C/s, with the maximum instantaneous temperature reaching 950°C. Furthermore, the thermal protection performance of superalloy honeycomb structure under simulated thermal environments was computed for different high heating rates by using 3D finite element method, and a comparison between calculational and experimental results was carried out. The results of this research provide an important reference for the design of thermal protection systems comprising superalloy honeycomb panel.